STRATEGIES TO CHANGE STUDENTS' NEGATIVE PERCEPTIONS ABOUT GUIDANCE AND COUNSELING TEACHER - Islahuddin, Muhammad (Transpublika Publisher, 2021)
The study aims to change students' negative perceptions of teacher guidance and counseling. This research method uses this literature review by looking for relevant literature that is done using databases such as Google Scholar. The findings of the Systematic Literature Review (SLR) study are that there are various strategies on the implementation of guidance and counseling programs in schools, the role of guidance and counseling teachers and collaboration between other parties related to the implementation of guidance and counseling programs in an effort to achieve the goals of comprehensive guidance and counseling itself. In the implementation of guidance and counseling programs there is optimal system support in the implementation of guidance and counseling programs because as an optimization on guidance and counseling program services provided to students. Keywords: Guidance and Counseling, Negative Perception, Comprehensive Guidance and Counseling